Creativity in persons at‐risk for bipolar disorder—A pilot study. Issue 5 (10th October 2018) - Burkhardt, Eva; Pfennig, Andrea; Breitling, Gwendolin; Pfeiffer, Steffi; Sauer, Cathrin; Bechdolf, Andreas; Correll, Christoph U.; Bauer, Michael; Leopold, Karolina
Abstract : Aim: The association between bipolar disorder and creativity may be related to symptoms of the disorder itself or personality traits present before the onset. To further explore the relationship between creativity and clinical risk for bipolar disorder, creativity among individuals with a history of depressive disorder and varying risk for future (hypo‐)manic episodes was assessed and compared. Methods: Thirty‐eight participants completed the diagnostic process, including Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM‐IV) Diagnosis, Hamilton Depression Scale and Young Mania Rating Scale. The early detection tools Bipolar Prodrome Symptom Interview and Scale‐Prospective (BPSS‐P), Early Phase Inventory for Bipolar Disorders (EPI bipolar ) and bipolar‐at‐risk‐(BAR) criteria were used to assign participants into different at‐risk groups. Assessment of creativity included Barron‐Welsh Art Scale (BWAS) and Creative Achievement Questionnaire (CAQ). Scores were compared between low‐ and high‐risk groups for the development of bipolar disorder. Results: Participants meeting BAR criteria scored significantly higher on the BWAS than the non‐BAR group ( P = 0.03). EPI bipolar groups did not differ significantly in creativity scores. Participants with mood swings, especially when associated with increased activity and euphoric features, had significantly higher BWAS scores compared to individuals without mood swings ( P = 0.04). Sleep disturbances, substance abuse, anxiety, ADHD and behavioural disturbances in childhood or adolescence had no effect on creativity level or achievement scores. Generalisability was reduced by small sample size and inclusion of depressive participants only considered at‐risk for bipolar disorder. Conclusions: There is evidence of increased creativity, but not of higher creative achievements, in persons at‐risk of bipolar disorder. Mood swings are strongly associated with creativity.